(untitled) (Indian Journal of Animal Production and Management, 2014)
A survey was carried out to study reproductive performances of swamp buffaloes of the undivided Kamrup, Nagaon and Darrang district of Assam. A total of 1293 randomly selected swamp buffaloes were included for the present study. Average age at first calving, gestation period, dry period, service period and intercalving period were found to be 52.28 ± 0.81 months, 323.10 ± 0.68, 252.84 ± 1.47, 177.34 ± 0.82 and 465.79 ± 1.67 days respectively. Age at first calving was not found to be affected significantly by type of animal and location while season of calving exerted significant effect (P<0.05). Gestation period was not found to be affected by type of animal, location, lactation order and season of calving. Dry period was found to be affected significantly (P<0.05) by location and highly significantly (P<0.01) by season of calving while type of animal and lactation order did not exert any effect. Service period was found to be affected significantly (P<0.05) by location and season of calving while type of animal and lactation order exerted non significant effect. Intercalving period was found to be affected highly significantly (P<0.01) by lactation order and significantly (P<0.05) by season of calving while type of animal and location exerted non significant effect.